Kesaksian Perempuan: Benarkah Separuh Laki-Laki? - al-Himmah, Lia Aliyah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
The fact that the Qur'an explicitly mentions about women as witnesses, and have the rights to receive inheritance is in itself a revolutionary advancement steps promoted by Islam for women's rights in the era. This means that the Qur'an acknowledges and recognizes not only women as individuals but also women's legal capacity and rights in social life, ideas that have never been observed by Arabian society of the seventh century. In this era women were denied access to inheritance, even they were seen as parts of objects of inheritance. Islam has radically changed this tradition by elevating women to be autonomous subjects of legal entity. Although the Chapter of Al-Baqarah verse 282 mentions about the necessity to have two women witnesses to replace one male witness, this should not mean that women are inherently inferior than men in terms of their capacity and rights to legal engangement. But we should see the spiritual message of this revolutionary offer provided by the Qur'an, that women can act as witnesses in business, in public affairs. Nowadays women have achieved and showed their intellectual and social capacity to be autonomous legal subjects, therefore the paper suggests that women can be witnesses in any businesses as far as they are knowledgable about the issues.